Skype - lessons learned from a history of success and failure in mergers and acquisitions - legal and financial aspects of intellectual property within the Skype acquisition - Aberham, Timon Matthias (2024)
The eventful acquisition history of Skype first gained attention in 2005 with eBay’s $2.6 billion takeover of the then-unprofitable VoIP technology company. After failed attempts to integrate the software into eBay’s bidding platform and an associated $1.4 billion write-down, legal disputes over the technology’s source code with Skype’s co-founders exposed the importance of intellectual property in the context of Mergers & Acquisitions. A subsequent majority stake sale to private equity investors at a $2.75 billion valuation and two attempted public floats later, Microsoft announced the staggering $8.5 billion acquisition that further illuminated challenges around intangible asset valuation and regulatory approval.